Computerize remote control car - Muhammad Shafiq, Mohd Shaberi (2016)
Computerized remote control car is the one project in the robotic field. This project is known as one of the robot platform that can be more develop into advance autonomous robot. The main feature of this project is it can be controlled wireless by using Android device. Android device nowadays have built in Bluetooth technology and one of the main our daily needs. This Bluetooth technology has been one of the most platforms in smartphone that was use in android system to develop an application to control all kind s of peripheral device like servo, DC gear motor, and others. RoboRemo software is the one of the software that can be use in developing Android app. The main objective of this project is to control the RC car and robot arm by using Android device through the Bluetooth communication. RoboRemo software will be installed on the Android device to create an application that can control the RC car and robot arm through Bluetooth. The implementation of the Android device for controlling RC car will solve a frequency problem that occurs while using RF transmitter. As the implantation of the Android device as controller of RC car can be apply by developing application using RoboRemo software.